2019
DOI: 10.1111/nbu.12410
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic inequalities in childhood obesity: Can community level interventions help to reduce the gap?

Abstract: A link between higher rates of childhood obesity and deprivation has been noted in the UK, as well as several other European countries and the US. The drivers of obesity are complex and multi‐factorial, but socially and economically disadvantaged groups may be more vulnerable to many of these. Evidence that rates of obesity are rising faster in low‐income population groups, resulting in widening inequalities indicates that prevention policies must take account of socio‐economic factors. It has been suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…In the UK, there is a clear socioeconomic pattern in child weight status,26 27 but whether this socioeconomic patterning is also clear in physical activity and/or sedentary behaviour among young people in the UK has yet to be determined. To the best of our knowledge, there has been no previous review focusing on data from the UK only.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, there is a clear socioeconomic pattern in child weight status,26 27 but whether this socioeconomic patterning is also clear in physical activity and/or sedentary behaviour among young people in the UK has yet to be determined. To the best of our knowledge, there has been no previous review focusing on data from the UK only.…”
Section: Introductionmentioning
confidence: 99%
“…Higher income and food security was also associated with more food waste in this study. Low consumption of fruit and vegetables is typically particularly evident among those on a low income, with diet quality being one example of socio‐economic health inequalities evident in the UK and elsewhere (Lockyer & Spiro ). Food waste occurring in a nation such as the UK in which individuals are experiencing food insecurity, evidenced by school holiday hunger and increased food bank use (The Conversation ), is difficult to reconcile.…”
Section: The Scale and Consequences Of Food Waste In The Ukmentioning
confidence: 99%
“…Furthermore, children from more deprived areas consumed, on average, 23% more calories daily compared to those from less deprived areas [23]. Similarly, a large international study that included children from the UK showed that obesity prevalence in 4-5 year old children living in the most deprived areas was more than double that of those living in the least deprived areas [24]. A further study from New Zealand investigated the association between neighborhood deprivation, unhealthy food outlets, unhealthy dietary behaviors, and children's weight status.…”
Section: Introductionmentioning
confidence: 97%